The Effects of Topical Corticosteroid Injection on Carpal Tunnel Syndrome - Mohammad Dehghani; Farinaz Sohrabi; Mahdi Teimouri (مجله دانشکده پزشکی اصفهان, 2012)
Background: The best treatment for mild to moderate carpal tunnel syndrome (CTS) is still controversial. The main aim of our study was to determine whether corticosteroid injection would result in a better outcome. Methods: In this randomized clinical trial, 88 individuals with mild to moderate CTS were selected from patients who referred to Kashani Hospital in Isfahan, Iran. The patients were randomly assigned into two groups. Splinting in neutral position of wrist was the only therapeutic method utilized in first group. However, splinting accompanied with corticosteroid injection was performed in the second group. Then the patients were evaluated in terms of pain intensity, and the relative prevalence of Phalen's and Tinel tests. Findings: Pain intensity and prevalence of Phalen's and Tinel tests were significantly lower in patients treated with splinting accompanied with corticosteroid injection. Conclusion: It seemed that splinting accompanied with corticosteroid injection is a more effective method in treatment of mild to moderate CTS.